(3GdJPjjd hGdJcejd aj TQM GdJSgjds - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf , (B745 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3jHOC HHGH (B((3GdeUOQ Gdejej(B): (3eG RjOJ Gdeje aj Chdg dZjQ eG JbOe hdjS HUaI s
(3BNQgG (B:s
(3bGd JYGdi(B: "(3cja jchf ddeTQcjf YgO YfO Gddg(B" (3Cj eG jchf ddeTQcjf BNQ GdLRA GdKGef jJdhg aj GdLRA GdJGSY s
(3JSgjd GdahGFO hJcejd GdebGUO dGHf eGdc GdWGFj GdLjGfj GdeJhai (B762(3g```s
(3fSNI KGdKIs
(3HgG fXGe GdJYbjHIs
(3hHChdgG Jedc SfI (B986(3g``` s
(3JHUQI GdYfhGf (B:s
(3JPjjds
Keywords: (3GdfMhs